GESTIÓN ADMINISTRATIVA - FINANCIERA Y SU RELACIÓN CON EL CUMPLIMIENTO DE METAS DEL GOBIERNO AUTÓNOMO DESCENTRALIZADO DEL CANTÓN PUEBLOVIEJO - Paucar Castro, Erika Carolina (2018)
In the city of Babahoyo, Province of Los Ríos, the research entitled "Administrative - Financial Management and its relationship with the fulfillment of goals of the Autonomous Decentralized Government of the Puebloviejo Canton" was carried out, whose main objective is to analyze the relationship between the Administrative - Financial Management with the fulfillment of goals of the Autonomous Decentralized Government of the Puebloviejo Canton in addition to identifying the incidence that exists between the Administrative - Financial Management and the fulfillment of goals of the Autonomous Decentralized Government of the Puebloviejo Canton, determining the extent to which the indicators contribute in the improvement of compliance of the goals, by implementing an improvement in the strategic guidelines and administrative-financial guidelines that contribute to the improvement of the fulfillment of the institutional goals. The research methodology to be implemented was descriptive, developed in the administrative and financial area of ​​the Autonomous Decentralized Government of the Puebloviejo Canton, applying interviews and surveys to a population of 45 people. The main problems found in the research do not allow to meet the requirements of the inhabitants, there is a slow process at the time of management, causing discomfort in the citizenry, in addition, it was observed in this public agency, that an adequate performance is not executed of internal control, mainly in the financial, administrative and operational processes, generating that decision-making is carried out in an orthodox manner and with a low technical and professional level that allows optimizing the use of public resources. Therefore, the strategic guidelines to be proposed would help to fully comply with the objectives and goals.